STUDENT CHARACTER BUILDING THROUGH HABITUATION OF DHUHA PRAYER AT SMA NEGERI 1 KASOKANDEL - Gina Hikmatul Ula; Nurul Hikmah; Nurul Senja Wiraning Fury (Cirebon International Conference on Education and Economics Proceeding, 2024)
Education creates a conducive environment where the main target is character building. The personality education that children get from their daily activities is often irregular and less systematic. Therefore, the sunnah dhuha prayer is used as a program that is expected to be able to create a golden generation of character in which the dhuha prayer is rarely used as a routine activity at school. This research was conducted to find out how the process of character building through the implementation of the dhuha prayer, and to find out the character formed from fostering students through the implementation of the sunnah dhuha prayer at SMA Negeri 1 Kasokandel so that the formation of good and religious student character can be attached to the student’s personality. This study uses a descriptive qualitative research type, carried out at SMA Negeri 1 Kasokandel. The subjects of this study were all students of class X, XI, and XII except non-Muslims who did not attend the dhuha prayer every Friday morning. This study shows the process of character building of students through habituation of the sunnah dhuha prayer. The dhuha prayer program at SMA Negeri 1 Kasokandel is held from 07.00 to 08.00 WIB, then with the hope of getting students to do the dhuha prayer in addition to the obligatory prayers and in the hope of forming character. The stages are, moral knowledge, moral feelings, and moral behavior. The methods used in character building are the method of habituation and self-development, the exemplary method, and the method of giving advice and attention. Then the characters that are instilled from habituation through dhuha prayers are the character of God’s love, the character of self-confidence and responsibility, and the character of discipline.